A STUDY ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMAN 1 PANGKALAN LESUNG IN WRITING DESCRIPTIVE TEXTS - Eva Marlini; Rumiri Aruan; Mahdum Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This descriptive research aims to find out the ability level of the first year students of SMAN 1 Pangkalan Lesung in writing descriptive texts. The population of this research are the first year students of SMAN 1 Pangkalan Lesung. The number of sample is 46 students who are chosen by using cluster random sampling technique. The data are collected using a writing test which contains one topic about “my favorite place”.The results of the data analysis showed that the mean score of the students’ ability in writing descriptive text is 61.68. It can be stated that the ability of the first year students of SMAN 1 Pangkalan Lesung in writing descriptive texts is good. Based on the result of the students’ ability in each writing aspect, the lowest score is in organization aspect and the highest score is in vocabulary aspect.Keywords: Study, Writing Ability, Descriptive Text.